Bagaimana Penerapan Pembelajaran Mendalam Pada Pengajar PAUD? - Laily Nurlina; Mulasih; Ratna Kartika Wati; Irma Galuh Prameswari (CV. Multi Kreasi Media, 2026)
The transformation of national education has encouraged educational inastitutions to implement student-centered learning that focuses on the holistic development of competencies. One of the approaches being promoted is deep learning, which emphasizes meaningful, reflective, and contextual learning experiences. However, the implementation of this approach in early childhood education still faces various challenges, particularly teacher’s limited understanding of its concept and implementation strategies. This community services program aimed to enhance the competencies of teachers at Aisyiyah Early Childhood Education Centers in Kebnaggan, Banyumas Regency, in understanding and implementing deep learning. The program was conducted through several stages, including needs assesment, concept dissemination, training workshops, lesson plan development practice, refelection, and evaluation. A total of 25 early childhood education teachers participated in the program, which was implemented using a participatory approach through interactive lectures, group discussions, learning video analysis, and group presentations. The results indicated and improvement in participants’ understanding of deep learning concept as well as their ability to design learning activities that integrated the dimensions of character development (olah hat), intellectual development (olah pikir), emotional and asesthetic development (olah rasa), and physical decelopment (olah raga0. Furthermore, participants demonstretad strong enthusiasm in developing more meaningful learning activities for young children. This program contributed to strengtheningbteacher’s pedagogical competencies and supported the implementation of educational transformation policies in early chlidhood education.